PENYULUHAN IMPLEMENTASI BELA NEGARA BAGI MASYARAKAT KELURAHAN REMPOA, KECAMATAN CIPUTAT TIMUR, TANGERANG SELATAN - Jerry Indrawan; Muhammad Prakoso Aji; Anwar Ilmar (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service activity (PKM) is carried out to provide information on the situation experienced by the community regarding changes in extension activities that are usually carried out directly. Due to the Covid-19 pandemic, outreach activities on the implementation of civic defense were carried out in online form. This online outreach was carried out using the Zoom Meeting application platform for 180 minutes. This counseling provided an explanation of the implementation of civic defense for the general public. The civic defense material presented was the meaning, values and goals of civic defense. In general, it can be concluded that the online outreach activity for the implementation of civic defense to the Rempoa Village provides an understanding that any Indonesian citizen can play an active role in realizing the values of civic defense in their daily life. KEYWORDS: PKM, online counseling, civic defense.